2014 International Conference on Electrical Machines (ICEM) 2014
DOI: 10.1109/icelmach.2014.6960211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the end-effects in magnetic gears and magnetically geared machines

Abstract: Magnetic gears and integrated magnetically geared machines have recently received much attention due to their exceptionally high torque densities. As in the design and analysis of conventional electrical machines, the finite element method (FEM) has been widely used for this class of electrical machine. For the sake of computational efficiency, the standard practice in FEM modeling is to reduce the problem complexity by applying only two-dimensional (2D) modeling and exploiting periodicity, if any. However, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 11 publications
5
24
0
Order By: Relevance
“…Fig. 5 shows the effect of the modulator thickness on the maximum torque of an MG [49]. Both 2D and 3D FE results confirm the existence of an optimum thickness corresponding to the stall torque of the MG.…”
Section: B Design and Analysis Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…Fig. 5 shows the effect of the modulator thickness on the maximum torque of an MG [49]. Both 2D and 3D FE results confirm the existence of an optimum thickness corresponding to the stall torque of the MG.…”
Section: B Design and Analysis Methodssupporting
confidence: 73%
“…The studies reported in [61] (2D FE) and [49] (3D FE) confirm that for an MG with fixed outer diameter, there exists an optimum gear ratio where torque capacity reaches a maximum.…”
Section: F Influence Of Mg Parameters On Torque Capabilitysupporting
confidence: 72%
See 2 more Smart Citations
“…7(a) by dashed line. It can be seen that, some of the flux coupling to the ferromagnetic polepieces does not penetrate through it, but returns to the same rotor as leakage flux [21]. On the other hand, the flux density concentration at the edges of ferromagnetic pole-pieces ( Fig.…”
Section: Operation Principle Of Afmgsmentioning
confidence: 96%